Trade and Domestic Financial Market Reform Under Political Uncertainty : Implications for Investment, Savings, and the Real Exchange Rate - Bhattacharya, Rina (IMF Working Papers; Working Paper, 2000)
This paper presents a model that incorporates uncertainty about trade reform and analyzes the effects of trade and financial liberalization on domestic investment and savings, the current account balance and the real exchange rate, both when the capital account is open and when it is closed. Under certain assumptions financial liberalization leads to a movement of resources in the opposite direction to that implied by trade liberalization and to real exchange rate appreciation, thus defeating one of the objectives of tariff reform, when the capital account is open. When political economy linkages are taken into account, however, the indirect effects of financial liberalization may offset the direct effects, encouraging a movement of resources in the desired direction. With a closed capital account these results should still hold unless there are strong negative income effects from trade reform.